The PIG in sPrInG: evidence on letter grouping from the reading of buried words. - Humphreys, G; Mayall, K; Cooper, A (2003)
We introduce a novel procedure for investigating factors that determine selective attention to letters in words. Participants were presented with words (in Experiments 1 and 3) and nonwords (in Experiment 2) that contained a buried word whose letters differed in color relative to the other letters present (e.g., pig, in spring). The strings were presented in single case or mixed case, keeping the letters of the buried words in one case (SpRiNg). The time in which the whole stimulus was named was shorter for same-case than for mixed-case strings (for spring: spring < SpRiNg). In contrast, the time in which buried words were named was shorter in mixed- than in same-case strings (for pig: spring > SpRiNg). Across items, the effects of case mixing were negatively correlated across the two tasks. The positive effect of case mixing for buried words also occurred irrespective of whether the whole string was a word or a nonword, and there were contributions from similarity of both letter size and case. The results suggest that case mixing can facilitate selective attention to letters, which is otherwise disrupted by size- and case-based grouping across letter strings. The study provides evidence for letter grouping using size and case information.